Review on the Future energy -Non Conventional Energy Resources - Sahni, Er. Karan; Singh, Er. Parwinder (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
In today’s time meeting the demand of energy is major concern for almost all the nations in the world .Due to the finiteness of fossil fuels and environmental degradation the development of non conventional energy resources is taking place quite rapidly .This paper describes briefly the various non conventional energy resources, their advantages, limitations and the places where these resources could be installed and India’s legal policies on non renewable energy resources